Improvement of sexual function in POEMS syndrome after combination therapy of Lenalidomide and dexamethasone. Issue 1 (December 2016) - Yang, Hongbo; Huang, Xufei; Cai, Qianqian; Wang, Chen; Cao, Xinxin; Zhou, Daobin; Li, Jian
Abstract Background POEMS syndrome is a rare paraneoplastic syndrome due to an underlying plasma cell neoplasm. Hypogonadism is the most common endocrine abnormality in POEMS syndrome. There is no data about improvement of hypogonadism and sexual dysfunction after appropriate treatment of POEMS syndrome so far. In this single-center prospective study, the efficacy of low-dose lenalidomide and dexamethasone combination therapy in the improvement of sexual and gonadal function in POEMS syndrome was evaluated. Results Thirty-five patients with newly diagnosed POEMS syndrome were treated with Lenalidomide (10 mg daily for 21 days) and dexamethasone (40 mg once per week) for 12 cycles. The international index of erectile function (IIEF) in male patients, the female sexual function index (FSFI) in female patients, total testosterone, estradiol and vascular endothelial growth factor (VEGF) levels were reviewed. Sexual dysfunction was reported in 88.8 % (24/27)male and 90.9 % (10/11) female patients. 62.9 % (17/27) male and 25.0 % (3/12) female patients had hypogonadism. After 12-month treatment, the mean total FSFI score had increased from 17.1 ± 7.2 to 23.7 ± 7.2(p < 0.05). The arousal, orgasm and sex pain domains had been improved significantly. The mean IIEF scores had increased from 12.9 ± 13.0 to 20.5 ± 18.4 (p < 0.05). Erectile function, sexual desire and intercourse satisfaction had improved significantly at the end of treatment. No association between VEGF levels and sexual function improvement was found in both genders. Conclusion Combination therapy with low-dose lenalidomide plus dexamethasone is successful in improving sexual function in POEMS syndrome.